Review of the genus Rhyparus Westwood, 1845 (Coleoptera: Scarabaeidae: Aphodiinae) in the Solomon Islands with description of two new species - Minkina, Łukasz; Skelley, Paul; Jákl, Stanislav; Král, David; Li, Xiao–Feng (Zootaxa, 2025)
A review of the genus Rhyparus Westwood, 1845 from the Solomon Islands is presented. First Solomon Islands records are presented for Rhyparus breviceps Paulian, 1984, and R. helophoroides Fairmaire, 1893. In addition, descriptions of two new species with illustrations are provided: Rhyparus guadalcanalensis Minkina, Skelley, Jákl, Král & Li, new species and Rhyparus malaitaensis Minkina, Skelley, Jákl, Král & Li, new species. A key to species of Rhyparus from the Solomon Islands is proposed.